METHODOLOGICAL FOUNDATIONS OF THE ANALYSIS OF THE SUSTAINABILITY OF THE DEVELOPMENT OF REGIONAL SOCIOECONOMIC SYSTEMS - Pulatov Abdulla, teacher (Western European Studies, 2024)
The article considers the main methodological approaches to the analysis of the sustainability of the development of regional socio-economic systems. A methodological approach to the analysis of the sustainability of the region's development is proposed based on the construction of typologies of municipalities as socio-economic subsystems on its territory and the assessment of generalizing indicators characterizing the completeness of the implementation of their external and internal functions.
Keywords: development; regional socio-economic system